(untitled) (Global Journal of Science Frontier Research, 2021)
This study was conducted to determine the effect of zinc on the productive performances, carcass yield and blood profiles of broilers. Experiment was done for a period of 35 days with a number of 60 day old broiler chicks. Birds were divided into four dietary treatment groups with 3 replications each having 5 birds per replication. The dietary treatment groups were; T 0 (basal diet; no zinc), T 1 (basal diet + 50 mg zinc/kg feed), T 2 (basal diet + 100 mg zinc/kg feed), T 3 (basal diet + 150 mg zinc/kg feed). Results indicated that body weight and body weight gain were increased significantly (P